Circular Economy Study in Indonesia: A Descriptive Approach to the Challenges and Opportunities of Its Implementation - Permana, Teguh; Puspitaningsih, Andriani (Institute Of Advanced Knowledge and Science, 2025)
This study aims to analyze the development, challenges, and opportunities for implementing a circular economy in Indonesia. A circular economy is a sustainable development approach that emphasizes resource efficiency through the principles of reduce, reuse, and recycle. This study uses a qualitative descriptive method with secondary data from government reports, academic publications, and international organizations. The analytical tool used is content analysis. The results of the study indicate that the implementation of a circular economy in Indonesia still faces various obstacles, including low public awareness, technological limitations, and regulations that are not yet optimally supportive. Nevertheless, the potential of a circular economy is enormous in supporting green economic growth and waste reduction. This study recommends the need for synergy between the government, the private sector, and the community in building a sustainable circular economy ecosystem.